2017
DOI: 10.1021/acs.biochem.7b00152
|View full text |Cite
|
Sign up to set email alerts
|

Heme Proximal Hydrogen Bonding between His170 and Asp132 Plays an Essential Role in the Heme Degradation Reaction of HutZ from Vibrio cholerae

Abstract: HutZ from Vibrio cholerae is an enzyme that catalyzes the oxygen-dependent degradation of heme. The crystal structure of the homologous protein from Helicobacter pylori, HugZ, predicts that Asp132 in HutZ is located within hydrogen-bonding distance of the heme axial ligand His170. Hydrogen bonding between His170 and Asp132 appears to be disfavored in heme-degrading enzymes, because it can contribute to the imidazolate character of the axial histidine, as observed in most heme-containing peroxidases. Thus, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…To confirm this, site--directed mutagenesis of Asp132 had previously been performed to reduce electron donation from His170. 37 Unexpectedly, replacement of Asp132 with Asn or Leu was shown to result in a decrease in heme--degradation activity, whereas replacement with Glu, which preserved the proximal hydrogen bond between His170 and Glu132, had little effect on this activity. This result suggests that the hydrogen bond between His170 and Asp132 is not a predominant factor in repressing the heme--degradation activity of HutZ.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 98%
See 1 more Smart Citation
“…To confirm this, site--directed mutagenesis of Asp132 had previously been performed to reduce electron donation from His170. 37 Unexpectedly, replacement of Asp132 with Asn or Leu was shown to result in a decrease in heme--degradation activity, whereas replacement with Glu, which preserved the proximal hydrogen bond between His170 and Glu132, had little effect on this activity. This result suggests that the hydrogen bond between His170 and Asp132 is not a predominant factor in repressing the heme--degradation activity of HutZ.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 98%
“…We previously observed the heme--degradation reaction under the single--turnover condition. 25,26,31,37 We here conducted the reaction in the presence of 2 equivalents of heme. When the reaction was initiated by the addition of HutZ to the solution containing 2 equivalent of heme, ascorbic acid and catalase, the heme--degradation ratio, defined as the ratio of iron concentration captured by ferrozine to the initial protein concentration, was ~160% ( Fig.…”
Section: Heme-degradation Activity Of Hutzmentioning
confidence: 99%
“…The structure of apo-HutZ was solved and its docking structure of heme predicted that Arg92 and His63 coordinate heme [18]. However, the results of our mutational studies suggested that His170 is a sole heme ligand, which was not coincident with the docking model [19,20]. The crystal structure of a HutZ homologous protein HugZ from Helicobacter pylori suggests that His170 of HutZ is the proximal heme ligand, which is within hydrogen bonding distance of Asp132 (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…The hydrogen bond between Asp132 and His170 could contribute to the imidazolate characteristic of proximal His170, as observed for most peroxidases [21][22][23]. To validate the importance of the proximal hydrogen bond in the heme degradation reaction, Asp132 or His170 was substituted in a previous study by our group [20].…”
Section: Introductionmentioning
confidence: 99%
“…[5] In addition to pH detection, the researches of protonated and deprotonated processes give a chance to view the structure-property relationship for functional dyes deeply. [6,7] Hydrogen bond plays an important role not only in the life process [8][9][10] but also in the construction of molecular systems. [11][12][13] Studies have shown that the formation of hydrogen bonds can inhibit the rotation between molecules, which can effectively immobilize the molecular structure, [14] and not only have an impact on the material melting point, boiling point, solubility, viscosity and other properties, [15] but also contribute to the nonradiative energy transitions of the excited state molecules, thus increasing the radiation transition.…”
Section: Introductionmentioning
confidence: 99%